Resignation letter from members of the Scottish Ambulance Unit (copy) - Crome, Leonard
1937-03-30 041-0022-004 -2- which had to be stopped. The last public distribution of food took place during the first week of February, from which date Miss Jacobsen distributed food privately. We feel that some of the food thus distributed did not go to the people for whom it was donated. Further than that, when Madrid was threatened by a dangerous advance from the Guadalajara sector, Miss Jacobsen discussed with members of the unit the possibility of remaining in Madrid behind General Franco's lines, should the rebels take the city. Provisional arrangements were actually made for this possibility. Two months after we had arrived in Spain, the internal situation in the unit became very serious, and one member who, naturally, took strong objection to the disservice which was being done to the Spanish Government by the purveying of atrocity stories, resigned from the unit. At this point, we, the undersigned, decided to discuss the matter fully with Miss Jacobsen, in order that the unit should continue to function, and that the actions of certain members should not harm the prestige of Scotland, of which the unit was a representative. To our surprise. Miss Jacobsen refused to deny the falsity of the stories, and actually gave credence to such statements, declaring, "There have been atrocities committed by both sides, and in any case one Spaniard is as good as another. We told Miss Jacobsen that such stories were fabrications, and that the purveying of them was a grave disservice to the Spanish Governnent, whose hospitality we enjoyed, and to the trust which the Spanish people had in us. We demanded that the two worst offenders be sent home so that the integrity of the unit could be maintained. Miss Jacobsen refused to do this, and we compromised to the extent of agreeing to continue our work with the unit if the two men were warned against continuing their harmful work. Two days later, however, and despite this warning, one of the two worst offenders again disseminated atrocity stories. This made our position in the unit untenable, and in order that we could fulfil the tasks for which the Scottish people sent us to Spain, we were forced 292/946/41/22(iv)